2020
DOI: 10.1016/j.braindev.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 in acute encephalopathy with biphasic seizures and late reduced diffusion

Abstract: Background:The initial presentation of acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is indistinguishable from that of complex febrile seizures (FS), which poses a great diagnostic challenge for clinicians. Excitotoxicity is speculated to be the pathogenesis of AESD. Vitamin B6 (VB6) is essential for the biosynthesis of gammaaminobutyric acid, an inhibitory neurotransmitter. The aim of this study is to investigate our hypothesis that VB6 deficiency in the brain may play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…rough aEEG monitoring of high-risk children with nerve injury, some studies have found that aEEG appears when obvious central nervous system damage occurs, especially in children with severe injury, aEEG has a specific abnormal map [13,14].…”
Section: Related Workmentioning
confidence: 99%
“…rough aEEG monitoring of high-risk children with nerve injury, some studies have found that aEEG appears when obvious central nervous system damage occurs, especially in children with severe injury, aEEG has a specific abnormal map [13,14].…”
Section: Related Workmentioning
confidence: 99%
“…Although data at the population level is lacking for vitamin B 1 deficiency compared to other micronutrients, studies on Chinese cohorts showed 91.8% of children and 81.7% of adults over 60 years do not reach their dietary estimated daily intake of vitamin B 1 ( Wang et al, 2017 ; Liu et al, 2019 ). Vitamin B 6 deficiency may manifest with seizures and other neurological events, because of the role of PLP in neurotransmitter biosynthesis ( Wilson et al, 2019 ; Akiyama et al, 2020 ; Rojo-Sebastián et al, 2020 ). Genetic defects in vitamin B 6 metabolism could also lead to vitamin B 6 -dependent epilepsy ( Wilson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 Consistent with this hypothesis, early initiation of vitamins and co-enzymes including vitamin B1, B6 and l-carnitine has been proposed as a therapy and can improve outcome in suspected AESD cases. 13,14 Early recognition is important, as delay has been shown to have cellular and molecular consequences. Shiihara and colleagues 15 reported that tau protein, a CSF biomarker of axonal damage, is elevated in children with AESD within the first 2 days of illness, suggesting that waiting to treat until the appearance of biphasic seizures or until BTA changes are observed may be too late to ameliorate pre-existing brain damage.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Consistent with this hypothesis, early initiation of vitamins and co-enzymes including vitamin B1, B6 and l -carnitine has been proposed as a therapy and can improve outcome in suspected AESD cases. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%